La participation du public au projet de paysage - Sonia Keravel (Projets de Paysage)
Landscape is a relationship between a subject and his environment ; it goes through us, transforms us and touches us. It constitutes more than a simple representation. Following this definition, the landscapers question increasingly the resonance that a work can find beyond a public : How can the public be integrated in the project process ? How can interaction be created ? Through the analysis of two cases (Henri Matisse park by Gilles Clément and Lancy Park by Georges Descombes), we propose to examine how the landscapers tend today to create conditions for meeting and exchange, by involving the user in the project, by inviting him to take part to it. We will highlight how the landscaper by enouncing no conclusive and open proposals, assumes new functions, closer to those of the mediator and the conveyor than the demiurge creator.